Synthetic engineering of central venous catheter based on antibacterial endothelial simulation can effectively antagonize vascular infection and thrombosis - Ling, Quan; Tian, Ye; Lv, Zhu; Chen, Jinling (Frontiers in Materials, 2025)
BackgroundInfection remains a prevalent complication affecting long-term central venous catheter (CVC) implantation. While nitric oxide (NO) demonstrates dual antibacterial and immunomodulatory potential, the therapeutic application of BNN6—a near-infrared-responsive NO donor—in CVC materials requires systematic validation. This study developed a BNN6-integrated polyurethane-polydopamine (PU-PDA) composite coating for CVCs, assessing its structural stability, biosafety, antimicrobial efficacy, and immunoregulatory capacity.MethodsThe PU-PDA matrix was engineered to encapsulate BNN6 for controlled release of NO. Material characterization included hemocompatibility profiling (hemolysis/coagulation assays) and antibacterial validation against Gram-positive/negative strains. Immunomodulatory effects were evaluated through scratch wound healing, transwell migration, and inflammatory mediator expression assays, with intracellular NO dynamics quantified via fluorescence imaging.ResultsThe composite coating exhibited optimal biocompatibility with negligible hemolytic activity (<2%). Bacterial proliferation was suppressed through NO-mediated metabolic disruption, while inflammatory cell motility demonstrated dose-dependent inhibition. Concurrently, upregulated intracellular NO correlated with reduced expression of pro-inflammatory cytokines (IL-6, TNF-α) and endothelial adhesion markers.ConclusionThe BNN6-PU-PDA system achieves spatiotemporal NO delivery, effectively attenuating microbial colonization and host inflammatory cascades through modulation of inflammatory mediators. This dual-action mechanism positions the material as a promising strategy for infection-resistant CVC development.